[INVITED] Design of turn around point long period fiber grating sensor with Au-nanoparticle self monolayer. (June 2018) - Bandyopadhyay, Sankhyabrata; Basumallick, Nandini; Bysakh, Sandip; Dey, Tanoy Kumar; Biswas, Palas; Bandyopadhyay, Somnath
Highlights: Influence of AuNP on the sensitivity of long period fiber grating (LPFG) has been investigated. Highly sensitive refractive index sensor has been designed. Theoretical model of a gold nanoparticle coated LPFG is proposed. Abstract: In this paper studies on the design and fabrication of a long period fiber grating (LPFG) with a self mono layer of gold nanoparticle (AuNP) has been presented. Refractive index (RI) sensitivity of a dispersed cladding mode (DCM) near turn around point (TAP) of its phase matching curve (PMC) has been investigated with and also without AuNP coated LPFG. The typical role played by the intermediate layer of AuNP on the effective index and thus on the sensitivity of the cladding mode to the surrounding RI has also been explored by carrying out coupled mode analysis of the requisite multilayer waveguide. Deposition of AuNP enhanced the sensitivity by more than a factor of 2. Measured sensitivity was found to be ∼3928 nm/refractive index unit (RIU) in the range of 1.3333–1.3428.